(untitled) (Clinics, 2006)
INTRODUCTION: Surgical lung biopsy is an invasive procedure performed when other procedures have failed to provide an urgent and specific diagnosis, but there may be reluctance to perform it in critically ill patients with diffuse pulmonary infiltrates. PURPOSE: To evaluate the diagnostic accuracy, the changes in therapy and survival of patients with diffuse lung infiltrates, mostly presenting acute respiratory failure, who underwent surgical biopsy. METHODS: We retrospectively examined medical records and surgical lung biopsies from 1982 to 2003 of 63 patients older than 18 years with diffuse infiltrates. Clinical diagnoses were compared to histopathological ones, from biopsies and autopsies. Laboratory and epidemiological data were evaluated, and their relationship to hospital survival was analyzed. RESULTS: All histological specimens exhibited abnormalities, mostly presenting benign/inflammatory etiologies. Fifteen patients had an etiologic factor determined in biopsy, most commonly Mycobacterium tuberculosis. The preoperative diagnosis was rectified in 37 patients. Autopsies were obtained in 25 patients and confirmed biopsy results in 72% of cases. Therapy was changed for 65% of patients based on biopsy results. Forty-nine percent of patients survived to be discharged from the hospital. Characteristics that differed significantly between survivors and nonsurvivors included sex (P = 0.05), presence of comorbidity (P = 0.05), SpO2 (P = 0.05), and presence of diffuse alveolar damage in the biopsy (P = 0.004). CONCLUSION: Surgical lung biopsy provided a specific, accurate etiologic diagnosis in many patients with diffuse pulmonary infiltrates when clinical improvement did not occur after standard treatment. Surgical lung biopsy may reveal a specific diagnosis that requires distinct treatment, and it would probably have an impact in lowering the mortality of these patients.